Effects of Ankle Muscle Fatigue and Visual Behavior on Postural Sway in Young Adults - Barbieri, Fabio A.; Penedo, Tiago; Simieli, Lucas; Barbieri, Ricardo A.; Zagatto, Alessandro M.; van Diëen, Jaap H.; Pijnappels, Mirjam A. G. M.; Rodrigues, Sérgio T.; Polastri, Paula F. (Frontiers in Physiology, 2019)
Ankle muscle fatigue has been shown to increase body sway. In addition, body sway in quiet upright standing is reduced when saccadic eye movements are performed. The purpose of this study was to investigate the effects of visual information manipulation on postural control during ankle muscle fatigue in young adults. Twenty young adults performed: 1) two 60-s trials in quiet bipedal standing with eyes open, eyes closed and while performing saccadic eye movements, 2) maximum voluntary isometric contractions in a leg press device, custom-made to test ankle plantar flexion force, 3) a calf raise exercise on top of a step to induce ankle muscle fatigue; 4) a repetition of items 1 and 2. Postural sway parameters were compared with two-way ANOVAs (vision condition X fatigue; p<0.05). Ankle muscle fatigue increased anterior-posterior and medial-lateral displacement, and RMS of sway, as well as sway area. Saccadic eye movements reduced anterior-posterior displacement and RMS of sway and area of sway compared to eyes open and eyes closed conditions. Both saccadic eye movements and eyes closed increased the frequency of AP sway compared to the eyes open condition. Finally, anterior-posterior displacement, anterior-posterior RMS, and both anterior-posterior and medial-lateral sway frequency were affected by an interaction of fatigue and vision condition. Without muscle fatigue, closing the eyes increased anterior-posterior displacement and RMS of sway, compared to eyes open, while during muscle fatigue closing the eyes closed reduced anterior-posterior displacement and had no significant effect on anterior-posterior RMS. In conclusion, body sway was increased after induction of ankle muscle fatigue. Saccadic eye movements consistently reduced postural sway in fatigued and unfatigued conditions. Surprisingly, closing the eyes increased sway in the unfatigued condition, but reduced sway in the fatigued condition.